2008
DOI: 10.1111/j.1553-2712.2008.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Mass Casualty Triage Skills Using Immersive Three‐dimensional Virtual Reality

Abstract: Objectives: Virtual reality (VR) environments offer potential advantages over traditional paper methods, manikin simulation, and live drills for mass casualty training and assessment. The authors measured the acquisition of triage skills by novice learners after exposing them to three sequential scenarios (A, B, and C) of five simulated patients each in a fully immersed three-dimensional VR environment. The hypothesis was that learners would improve in speed, accuracy, and self-efficacy.Methods: Twenty-four me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 10 publications
4
64
0
Order By: Relevance
“…VRS is experientially reported to help learners achieve learning outcomes [11,19,[22][23][24] . Participants' self-report that these environments are realistic and not difficult to use [6,17] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…VRS is experientially reported to help learners achieve learning outcomes [11,19,[22][23][24] . Participants' self-report that these environments are realistic and not difficult to use [6,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Knight, Carley, Tregunna, Smithies, deFreitas, Dunwell and Machway-Jones [23] discovered that triage tagging accuracy and triage step accuracy was significantly higher in a VRS training group than the group trained using a card sort exercise with no difference in time to triage (n = 91). Vincent et al [19] , found improvement in triage scores (mean=6.5, Std=.83 on a 7 point scale), speed and self-efficacy (p=.001) after fully immersive VRS. The use of student volunteers in this study may have resulted in more technically sophisticated participants and because student were used as their own controls the increase in the scores may have been due to repetition of the scenario.…”
Section: Participant Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…case study #2: Mass casualty Triage Vr Vincent et al (2008) developed an immersive VR system for teaching mass casualty triage skills. The system consisted of an HMD, stereo earphones, and three electromagnetic sensors for tracking the head and both hands.…”
Section: Technique #2: Abstracted Objectsmentioning
confidence: 99%